Factors influencing the effectiveness of music communication in Disney animated films - Jiang, Jinli; Srijinda, Prakaikavin (Edelweiss Applied Science and Technology, 2025)
This study takes Disney animated film music as the subject of music communication. It discusses the key factors that influence the communication effect of Disney animated film music on listeners in the new media era. This study uses the theoretical framework of Technology Acceptance Theory and quantitative research methods. They are combined with the Technology Acceptance Model (TAM), which provides an in-depth understanding of the influence of Disney animated film music on the cognitive effect, emotional attitude effect, and behavioral effect of listeners. The findings reveal several essential factors influencing the communication effects of Disney animated film music, including listeners' cognitive level, the music, the emotional resonance of the music, and attitudes and behaviors of music communication. These findings not only optimize the communication strategy and audience experience of Disney animated film music but also provide a theoretical basis and practical reference for communication suggestions to improve the communication effect of Disney animated film music.